The Influence of Social Media Influencers on Generation Z Consumer Behavior in Indonesia - Erwin Erwin; Siska Jeanete Saununu; Arief Yanto Rukmana (Westscience Press, 2023)
Through a quantitative approach, this study examines how social media influencers affect Indonesian Generation Z consumer behavior. A heterogeneous group of 450 participants, ranging in age from 16 to 24, was involved, reflecting a range of genders, socioeconomic backgrounds, and geographic locations. The results show that social media influencers have a big influence on people's decisions to buy, as 85% of participants acknowledged. The majority platform, Instagram, accounted for 75% of the total, with individuals using social media for two hours a day on average. The most popular content categories (65%) were product and lifestyle reviews, highlighting the significance of authenticity. Transparency (72.5%) and authenticity (67.5%) were important trust-building qualities; on the other hand, inconsistent brand endorsements (30%) and a lack of financial transparency (22.5%) eroded confidence. Sponsored material worked very well (80%), and 60 percent of users preferred partnerships that were authentic. Strong positive correlations between sponsored content, consumer behavior, and influencer engagement were found via regression analysis (R-squared = 0.754). The findings offer significant perspectives for marketers seeking to maneuver through the impactful terrain of Generation Z in Indonesia.